French Rococo Ébénisterie in the J. Paul Getty Museum - Wilson, Gillian (Getty Publications, 2021)
The first comprehensive catalogue of the Getty Museum's significant collection of French Rococo ébénisterie furniture. This catalogue focuses on French ébénisterie furniture in the Rococo style dating from 1735 to 1760. These splendid objects directly reflect the tastes of the Museum's founder, J. Paul Getty, who started collecting in this area in 1938 and continued until his death in 1976. The Museum's collection is particularly rich in examples created by the most talented cabinet masters then active in Paris, including Bernard van Risenburgh II (after 1696-ca. 1766), Jacques Dubois (1694-1763), and Jean-François Oeben (1721-1763). Working for members of the French royal family and aristocracy, these craftsmen excelled at producing veneered and marquetried pieces of furniture (tables, cabinets, and chests of drawers) fashionable for their lavish surfaces, refined gilt-bronze mounts, and elaborate design. These objects were renowned throughout Europe at a time when Paris was considered the capital of good taste. The entry on each work comprises both a curatorial section, with description and commentary, and a conservation report, with construction diagrams. An introduction by Anne-Lise Desmas traces the collection's acquisition history, and two technical essays by Arlen Heginbotham present methodologies and findings on the analysis of gilt-bronze mounts and lacquer.